Association of acute disseminated encephalomyelitis (ADEM) and COVID-19 in a pediatric patient - Chen, Liam (Free Neuropathology, 2021)
Cases of acute disseminated encephalomyelitis (ADEM) and its hyperacute form, acute hemorrhagic leukoencephalitis (AHLE), have been reported in coronavirus disease 2019 (COVID-19) patients as rare, but most severe neurological complications. However, histopathologic evaluations of ADEM/AHLE pathology in COVID patients are extremely limited, so far having only been reported in a few adult autopsy cases. Here we compare the findings with an ADEM-like pathology in a pediatric patient taken through a biopsy procedure. Understanding the neuropathology may shed informative light on the autoimmune process affecting COVID-19 patients and provide critical information to guide the clinical management.